(untitled) (Journal of the College of Languages (JCL), 2014)
Desde la Salamanca de doradas piedras que tantas veces cantara, don Miguel de Unamuno dio a la literatura y al pensamiento españoles unas obras que, a pesar de muchos pesares, perdura viva, como viva fue su agónica existencia. El bilbaíno Miguel de Unamuno (1864-1936) es autor de al menos, doce obras teatrales. Su costumbre de mezclar géneros literarios, sin distinguir claramente el drama de la novela dialogada, le llevó a preferir el teatro leído. De ahí que sus estrenos fuesen, frecuentemente, muy posteriores a las ediciones impresas. Abstract: The Bilbao Miguel de Unamuno (1864-1936) is the author of at least twelve plays. His habit of mixing genres, without clearly distinguishing the drama of the novel in dialogue led him to prefer the theater read. Hence their releases were frequently much later than the printed editions. Writer tirelessly newspaper articles, essays, short stories, novels, dramas, poems thousands of interesting, and again the same themes are repeated, either in tragic tone as nothing less than a real man (1920), in tone metaphysical burlesque and Fog (1913, probably the best novel of its generation) or the anguished meditations of his poetry. In their fields will see all things simple and brief (about the events or characters). Participated in politics and writes about it from radical liberal positions. In exile during the dictatorship, Europe becomes a symbol of the fight republican. And sharpens its conflict between the "I" we are or think we are and the "I" that we are to others.